Feasibility of robot-assisted radical prostatectomy in men at senior age ≥75 years: perioperative, functional, and oncological outcomes of a high-volume center. (27th December 2022) - Leyh-Bannurah, Sami-Ramzi; Wagner, Christian; Schuette, Andreas; Liakos, Nikolaos; Karagiotis, Theodoros; Mendrek, Mikolaj; Rachubinski, Pawel; Oelke, Matthias; Tian, Zhe; Witt, Jorn H.
Abstract: Objectives: The aim of this study was to assess whether age ≥75 years impairs surgical, functional, and oncological outcomes after robot-assisted radical prostatectomy (RARP). Materials and methods: Patients with prostate cancer (PCa) were stratified in ≥75( n = 669) vs. <70 years( n = 8, 268). Multivariable cox regression analyses (MVA) tested for effect of senior age on erectile function-, urinary continence-recovery, biochemical recurrence (BCR), and metastatic progression (MP). Results: RARP duration, blood loss, and 30d complication rates were similar between groups. For patients ≥75 vs. <70 years, rates of erectile function after 36 and urinary continence after 12 months were 27 vs. 56% ( p < 0.001) and 85 vs. 86% ( p = 0.99), respectively. Mean quality of life (QoL) score after 12 months improved in both groups ( p = 0.9). At 48 months, BCR- and MP-free rates were 77 vs. 85% ( p < 0.001) and 97 vs. 98% ( p = 0.3), respectively. MVA confirmed the negative effect of senior age on erectile function but no significant effect on urinary continence, BCR or MP, before and after propensity score matching. Conclusion: Apart from erectile function, senior age has no significant effect on urinary continence recovery, BCR- or MP-free rates after RARP. Post-RARP QoL improved even in senior patients. Modern therapy of senior PCa patients should be based on individual counseling than just age.